REVIEWS - Davies, Philip R. (Journal of Semitic studies, 2003)
Exile: Old Testament, Jewish & Christian Conceptions (SJSJ 56) James M.Scott (ed.). Brill, Leiden 1997. Pp. 385 cloth. Price: $103.75 . ISBN: 90-04-10676-6.